Investigation of the effect of anti-epileptic drugs on bone metabolism using osteoprotegerin and bone-specific alkaline phosphatase: The direct effects of antiepileptic drugs on bone metabolism - Tuğan Yıldız, Buket; Koca, Tuba Tülay; Seyithanoğlu, Muhammed; Altıntaş Aykan, Duygun (Journal of Surgery and Medicine, 2021)
Background/Aim: Anti-epileptic drugs are long-term medications; thus, side-effects are frequently seen. An important but insufficiently known side-effect is the emergence of metabolic bone diseases. The mechanism of this entity is not clearly known, but it is usually seen with the use of cytochrome P450 enzyme-inducing anti-epileptics. However, recent studies demonstrated that non-enzyme-inducing molecules also cause bone mineral impairment. The aim of this study was to shed light on the pathogenesis of anti-epileptic metabolic bone disease using bone turnover markers. Methods: This comparative, prospective case-control study included 37 patients followed-up in our outpatient clinic and 39 healthy control subjects. All the patients were female, aged over 18 years and in the premenopausal period, and had received the same anti-epileptic treatment for at least 3 months. Male patients, females who were <18 years old, pregnant, in the postmenopausal period, those with osteoporosis, gastrointestinal malabsorption, physical impairment that may prevent normal ambulation, endocrine and metabolic disease, musculoskeletal and joint disease or a history of medication use were excluded from the study. A healthy control group was formed of age-matched premenopausal women, with no disorders causing gastrointestinal malabsorption, no physical impairment preventing normal ambulation, no endocrine or metabolic disorder, or history of medication use that may affect bone turnover. The levels of serum calcium, alkaline phosphatase, 25-hydroxyvitamin D, osteoprotegerin and bone-specific alkaline phosphatase were assessed, and the results were recorded. Results: Evaluation was made of 37 female epilepsy patients with a mean age of 30.8 (8.1) years and a healthy control group of 39 age- and body mass index-matched females (P=0.69, P=0.85, respectively). The mean duration of AED use was 6.1 (5.5) years. The calcium (P=0.09), phosphate (P=0.906) and alkaline phosphatase (P=0.22) levels were similar in both groups. The levels of 25-hydroxyvitamin D (P=0.049), osteoprotegerin (P=0.025), and bone- specific alkaline phosphatase (P=0.037) were significantly lo3wer in the epilepsy group. Conclusion: Our study showed that serum levels of osteoprotegerin and bone-specific alkaline phosphatase, which are markers of increased bone formation, were lower in epilepsy patients. Probably many factors cause the bone mineral disorder seen in epilepsy patients. Antiepileptic use is one of them. These results suggest that antiepileptics may not only affect enzyme induction but also bone turnover. Neurologists should be aware of this issue and monitor patients regularly with respect to bone mineralization to enable early treatment when necessary.